Clinical course, long-term outcomes, and Chemotherapy toxicity profile in B-cell Non-Hodgkin Lymphoma in children: single institution experience of Pakistan - Rehman, Palwasha; Wali, Rabia Muhammad (Journal of the Pakistan Medical Association, 2022)
Objective: To analyse the disease presentation, clinical course and long-term outcomes of children diagnosed with B-cell non-Hodgkin lymphoma. Method: The retrospective descriptive study was conducted at the Shaukat Khanum Memorial Cancer Hospital and Research Centre, Lahore, Pakistan and comprised data of patients diagnosed with B cell non-Hodgkin lymphoma between January 2012 and December 2016, with follow-up time of 4 years post-treatment. Data was collected from the institutional database. Data was analysed using SPSS 20. Results: Of the 286 patients, 217(75.6%) were males and 69(24.1%) were females. The overall mean age at presentation was 7.6±4.1 years (range: 1-16 years). Burkitt lymphoma was diagnosed in 194(67.8%) patients, and diffuse large B cell in 83(29.0%). Majority of patients had presented with stage III disease 159(55.6%). Complete remission was achieved in 173(60.5%) patients, while 90(31.5%) died during treatment. The 4-year overall survival observed was 67.1%, whereas event-free survival was 60.5%. Conclusion: Majority of the paediatric patients presented with extensive disease. Measures are needed for early recognition, identification, and prompt referral to paediatric cancer institute. Key Words: B cell origin, Children, Non-Hodgkin lymphoma, Outcome.